Pengaruh GDRP Per Kapita, Pengeluaran Kesehatan, Pengeluaran Perlindungan Sosial Dan IPM Terhadap Kemiskinan di Provinsi Sumatera Selatan Tahun 2015-2021 - Elvinda Rosa (Balitbangda Provinsi Jambi, 2024)
This study aims to determine the effect of GRDP per capita, expenditure on health expenditure on social protection and the human development index on poverty in regency/city in South Sumatra Province in 2015-2021.The type of research is descriptive quantitative with panel data regression analysis method. The results showed that GRDP per capita and the human development index had a significant negative effect on the poverty rate. Expenditure on health and expenditure on social protection has a positive but insignificant effect on poverty rate in districts / cities in South Sumatra Province in 2015-2021.